Piutang, Utang, dan Biaya Produksi Terhadap Profitabilitas Perusahaan Pada Perusahaan Manufaktur Sub Sektor Farmasi - Yustin Triastuti; Krisna Sudjana; Fidiana Putri (Journal of Academia Perspectives, 2022)
In the business world of course every company has a variety of sales strategies, one of which is by selling credit, the sale of these credits that will lead to receivables.. The purpose of this writing is to determine the effect of receivables, debt and production costs on the profitability of manufacturing companies listed in IDX in 2017-2019. To find out. The purpose of this writing is to determine the effect of receivables, debt and production costs on the profitability of manufacturing companies listed in IDX in 2017-2019. To find out. Secondary data used in this study in the form of financial statements of 9 manufacturing companies registered with IDX. The analysis method used is to perform calculations on each variable, descriptive test, classic assumption test, multiple linear regression, F test and T test aimed at obtaining results on variable X and Y whether partially or simultaneously influential. Based on the results of the partial study, the turnover of receivables has a calculated t value of 0.455 and a significant level of 0.654. With a sig value. 0.654 > 0.05 then Ho was rejected, so it can be concluded that the turnover of receivables has no significant effect on Profitability